KEADILAN AKSES MERATA PENDIDIKAN ANAK USIA DINI BAGI MASYARAKAT DI DAERAH 3T (TERDEPAN, TERLUAR, DAN TERTINGGAL) - Safira Nada Agustin; Siti Nur Ghaniyah; Wawan Setiawan; Zaenul Slam (STKIP Subang, 2026)
Library research that focuses on reasoning, tracing, and analyzing sources of scientific articles. The purpose of this research is to analyze and critique various issues of unequal access, especially in early childhood education (PAUD), by linking human rights and Pancasila as indicators of official scientific sources. The research results show that 3T areas find it very difficult to access education due to limited locations and personel, as well as the strong influence of various factors. 3T areas should be prioritized because of the limited educational locations and teaching staff in those regions. The fundamental rights of children must be fulfilled by parents, and the government should create policies that provide ease to lower-income communities, especially in 3T areas. A very important strategy to implement is to provide social assistance or educational aid to lower-income communities and in 3T areas. Equal distribution of facilities and Infrastructure in educational institutions in underdeveloped, frontier, and outermost regions. Educators, the community, and the government must expand educational assistance programs to all regions and develop inclusive education for children with disabilities and those from underprivileged backgrounds. Realizing every child will have their rights and Pancasila values fulfilled. Realizing justice and expanding all facilities and Infrastructure, of high quality in 3T areas or among vulnerable groups, is an important manifestation for society.